2007
DOI: 10.1016/j.dam.2007.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Triangle-free graphs with uniquely restricted maximum matchings and their corresponding greedoids

Abstract: A matching M is uniquely restricted in a graph G if its saturated vertices induce a subgraph which has a unique perfect matching, namely M itself [M.C. Golumbic, T. Hirst, M. Lewenstein, Uniquely restricted matchings, Algorithmica 31 (2001) 139-154]. G is a König-Egerváry graph provided (G) + (G) = |V (G)| [R.W. Deming, Independence numbers of graphs-an extension of the König-Egerváry theorem, Discrete Math. 27 (1979) 23-33; F. Sterboul, A characterization of the graphs in which the transversal number equals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The following lemma, firstly presented in [20], shows that every König-Egerváry graph with a unique perfect matching has at least one leaf (see, for example, the graph G 1 , depicted in Figure 1). We give a proof here for the sake of selfcontainment.…”
Section: Resultsmentioning
confidence: 99%
“…The following lemma, firstly presented in [20], shows that every König-Egerváry graph with a unique perfect matching has at least one leaf (see, for example, the graph G 1 , depicted in Figure 1). We give a proof here for the sake of selfcontainment.…”
Section: Resultsmentioning
confidence: 99%
“…Theorem 1.9 [19] If G is a triangle-free graph, then Ψ(G) is a greedoid if and only if all maximum matchings of G are uniquely restricted and the closed neighborhood of every local maximum stable set of G induces a König-Egerváry graph.…”
Section: Theorem 18 [17] For a Bipartite Graph G ψ(G) Is A Greedoidmentioning
confidence: 99%
“…S is called a local maximum stable set of G, and we write S ∈ Ψ(G), if S is a maximum stable set of the subgraph induced by the closed neighborhood of S. A greedoid (V, F) is called a local maximum stable set greedoid if there exists a graph G = (V, E) such that F = Ψ(G).Nemhauser and Trotter Jr. [27], proved that any S ∈ Ψ(G) is a subset of a maximum stable set of G. In [15] we have shown that the family Ψ(T ) of a forest T forms a greedoid on its vertex set. The cases where G is bipartite, triangle-free, well-covered, while Ψ(G) is a greedoid, were analyzed in [17], [19], [21], respectively.In this paper we demonstrate that if G is a very well-covered graph, then the family Ψ(G) is a greedoid if and only if G has a unique perfect matching.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S is a local maximum stable set of G, and we write S ∈ Ψ(G), if S is a maximum stable set of the subgraph induced by S ∪ N (S), where N (S) is the neighborhood of S.Nemhauser and Trotter Jr. [20], proved that any S ∈ Ψ(G) is a subset of a maximum stable set of G. In [12] we have shown that the family Ψ(T ) of a forest T forms a greedoid on its vertex set. The cases where G is bipartite, triangle-free, well-covered, while Ψ(G) is a greedoid, were analyzed in [14], [15], [17], respectively.In this paper we demonstrate that if G is a very well-covered graph of girth ≥ 4, then the family Ψ(G) is a greedoid if and only if G has a unique perfect matching.…”
mentioning
confidence: 99%